Prediagnostic serum selenium levels in relation to breast cancer survival and tumor characteristics. Issue 9 (18th May 2020) - Sandsveden, Malte; Nilsson, Emelie; Borgquist, Signe; Rosendahl, Ann H.; Manjer, Jonas
Abstract: Women with lower levels of serum selenium (Se) may have a worse survival in breast cancer than women with higher levels, despite no difference in incidence of the disease. Our study was conducted to test whether Se is associated with the aggressiveness of breast tumors. Both the risk of having a tumor characteristic associated with worse prognosis, as well as the overall and breast cancer‐specific mortality, were studied. We identified breast cancer cases and controls within the Malmö Diet and Cancer Study, a population‐based cohort with 17 035 women recruited between 1991 and 1996. Inclusion criteria were incident breast cancer. Exclusion criteria were carcinoma in situ and bilateral breast cancer. Controls were selected among breast cancer‐free women both from matching (n = 694) as well as randomization (n = 492). After exclusion, 1066 cases remained and were compared to controls regarding their prediagnostic serum Se levels and subsequent risk of having a certain tumor characteristic or intrinsic subtype. We also followed breast cancer patients regarding overall and breast cancer‐specific mortality, comparing different Se quartiles. No association between serum Se quartile and any tumor characteristic or intrinsic subtype was found. Lower overall mortality was found among women in the highest Se quartile compared to the lowest using an adjusted Cox proportional hazards model, hazard ratio 0.63 (95% confidence interval: 0.44‐0.89). Similar results were seen for breast cancer‐specific mortality, 0.60 (0.37‐0.98). The results of our study support that Se is associated with a lower mortality in breast cancer, not related to established prognostic factors. Abstract : What's new? While selenium may have little effect on the overall risk of breast cancer, its effect on breast cancer prognosis is yet to be established. Here, the authors studied the association between pre‐diagnostic serum selenium level and breast cancer aggressiveness and mortality in 1, 066 breast cancer patients compared to controls. They found better breast cancer‐specific and overall survival among women with higher pre‐diagnostic selenium levels. However, no correlation between selenium status and specific breast cancer characteristics or intrinsic subtype was found. Altogether, the findings suggest that selenium is an independent prognostic factor for mortality in breast cancer patients.